2019
DOI: 10.1002/app.47403
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel silicon‐containing hybrid polymer by thermal curing, pyrolysis behavior, and fluorescence analysis

Abstract: A novel linear silicon‐containing hybrid polymer with C  C and SiH linkages, diphenyl‐dihydroethynyl‐silane (DPHES), had been conveniently synthesized and well characterized. The thermal curing, crosslinked structure and pyrolysis behavior were studied by DSC, Fourier transform infrared (FTIR), and Pyrolysis‐gas chromatography/mass spectrometry (Py‐GC/MS). The results suggest the crosslinked structures consist mainly of phenyl and aromatic fused rings, which are formed through cyclotrimerization, addition re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The information obtained by the technique derives from the type of chemical product derived from pyrolysis. Each polymer is characterized by its own degradation products and ions that are exploited for identification (Chen et al, 2019 ; Yang et al, 2019 ). It has advantages and limitations.…”
Section: Methodsmentioning
confidence: 99%
“…The information obtained by the technique derives from the type of chemical product derived from pyrolysis. Each polymer is characterized by its own degradation products and ions that are exploited for identification (Chen et al, 2019 ; Yang et al, 2019 ). It has advantages and limitations.…”
Section: Methodsmentioning
confidence: 99%
“…Microplastics ("MP") pollution, especially in the marine environment, has become a serious global problem with farreaching consequences [1][2][3] . Plastic production has been steadily increasing over the past few decades, surpassing 400 million tons in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic production has been steadily increasing over the past few decades, surpassing 400 million tons in 2020. Forecasts show that by 2050 it can reach more than 1000 tons of dollars [1][2][3] . The longevity and complete biodegradability of plastic has led to the accumulation of approximately 9,200 million tons of plastic waste on our planet between 1950 and 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon-containing arylacetylene (PSA) resins can be used as the matrixes of advanced polymer composites because of their excellent performance, such as no curing volatiles, high decomposition temperature, and high char yield after pyrolysis. Itoh et al synthesized the first kind of PSA, poly­[(phenylsilylene)­ethynylene-1,3-phenyleneethynylene] (abbreviated MSP in their work) . They found that these resins are highly heat-resistant, nonflammable, and moldable, which have a 5% decomposition temperature ( T d5 ) of 860 °C and the residue at 1000 °C of 94%.…”
Section: Introductionmentioning
confidence: 99%